OPEN BORDERS OF THE EUROPEAN UNION: NATIONAL AND EUROPEAN IDENTITY ON THE EXAMPLE OF CERTAIN EU MEMBER-STATES - E. V. Khakhalkina; K. P. Andreev; G. V. Grosheva; I. A. Kochev (Vestnik MGIMO-Universiteta)
During the acute phase of the migration crisis (2014–2015) in a large number of European Union states, policies restricting internal borders and the strengthening of external borders took place, which raised serious questions about the future of the European Union’s borders. Ever since the emergence of supranational structures, freedom of movement, capital, goods, services and labor has all been the principal focus points of the EU countries cooperation. The uncertain nature and complexlexity regarding migration issues, strengthening of Eurosceptic sentiments in certain EU countries, the commitment to population in certain member states, the EU’s future and its main achievements (including such issues as freedom of borders, which is still under threat of illegal migration and criminal-terrorist elements) remain a big question.The authors of the article aim to evaluate the current state and threats to open borders of the European Union using analysis of common European identity. One of its elements includes the population’s attitude to issues such as the mobility and freedom of borders and their relation with national identity on the example of different EU countries, which consistently support and/or criticize the existing supranational model.In the first part of the article, the author discuss’ the main causes for why the EU borders at present have grown so important. Also, their correlation to the task of strengthening solidarity and trust throughout the EU, by overcoming a common European identity crisis.In the second part of the article the process of forming a common European identity and the reflection of this concept in the basic documents of the EU are presented retrospectively. In the third part the place of migration and its relation to the problem of borders in national and European identities through the example of EU member-states is illustrated by the example of countries whose population is both European oriented and by Eurosceptic states. In the final section conclusions are drawn regarding the importance of «open borders» for the EU in medium and long term outlook.